A Dual-Amplification Electrochemical Aptasensor for Profenofos Detection. Issue 2 (21st January 2020) - Zhang, Hui; Sun, Jianfei; Cheng, Shuting; Liu, Huimin; Li, Falan; Guo, Yemin; Sun, Xia
Abstract : The present study reported a dual-amplification electrochemical aptasensor for sensitive detection of profenofos (PFF) in vegetables. A screen-printed carbon electrode (SPCE) modified with graphitized multi-walled carbon nanotubes (MWCNTGr ) and Au nanoshell was used as a test platform, which ensured a rapid detection process and showed a favorable electrochemical performance. MWCNTGr and Au nanoshell enhanced the electrical conductivity and the surface area, thus the detection signal was amplified. The affinity between PFF and its aptamer (Apt) was verified firstly by dot blot hybridization (DBH), and the result was exciting. Furthermore, the effects of the aptamers modified respectively with -NH2 and -SH on the current signal were compared with each other by cyclic voltammetry (CV), and results showed that the aptamers modified with -NH2 made the current signal change more obvious. Based on all above, a high-efficiency electrochemical aptasensor was fabricated with a wide linear range from 0.1–1 × 10 5 ng · ml −1 and a detection limit of 0.052 ng · ml −1 under the optimized conditions. This aptasensor had great specificity, stability and reproducibility. Hence, the developed aptasensor was successfully used to detect PFF in vegetables. The proposed method also has a potential for the detection of other organophosphorus pesticide (OPs).